Antibacterial Activity And Phytochemical Screening From Chromatography Fraction Of Ethanol Extract Of Sarang Banua (Clerodendrum fragrans Vent Willd) Against Salmonella enterica - Murniaty Simorangkir; Ade Pratiwi Maha (Universitas Negeri Medan, 2020)
Ethanol extract of sarang banua leaves (Clerodendrum fragrans) has biological activity. This study aims to isolate the fraction of ethanol extracts of Sarang Banua leaves (Clerodendrum fragrans) and test their antibacterial activity against Salmonella enterica. The isolation method uses the vacuum liquid chromatography method, with eluent n-hexane, ethyl acetate and methanol with increasing polarity levels. Antibacterial activity was carried out by the inhibitory test, the MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration). The results showed that the FC fraction chromatographic results of the vacuum column of ethanol extract of Sarang Banua leaf (Clerodendrum fragrans) had antibacterial activity against Salmonella enteric with a strong inhibitory power (inhibitory zone 18.25 mm), MIC value of 125 µg / mL and MBC value of 125 µg / mL are included in the medium category. Inhibition, MIC and MBC values of chloramphenicol (positive control) against S. enterica were 17.40 mm; 31.2 μg / mL and 62.5 μg / mL. In the FC fraction there are higher amounts of secondary metabolites flavonoids, tannins, as well as small amounts of alkaloids, saponin, steroids dan triterprnoids.